Becoming Witnesses Of The Living Christ : Faith Formation Series - Epafras Mujono; Rut Melisa Martalen H (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service Activities have several background problems, namely: First, there is a shift in understanding of the meaning of testifying about Jesus to other people. More and more people understand that witnessing about Jesus is enough just by the life and good deeds of believers, if we look at the context of our current society. Second, it is often misunderstood by believers in Jesus regarding 'good deeds to others', because salvation is only by grace and by faith alone. Therefore, the purpose of this activity is: First, to explain ways to be good witnesses of Christ and testify through our good deeds. Second, to measure the level of respondent satisfaction with the material and delivery of this activity. The method used to present this article is the descriptive method, while the method used in the activity is the lecture method. The results of this activity are: First, ways to be a good witness for Christ (Acts 4:13-20), namely having the right belief in Jesus, acting rightly and having the right priorities. Meanwhile, the principles of witnessing through good deeds are doing good with gentleness, doing good when bearing burdens, doing good because there is a law of sowing and reaping from God. Second, the results of audience satisfaction are as follows: Of the 116 samples who responded to the satisfaction level questionnaire: no people (0%) said they were dissatisfied, 0.5 people (0.44%) said they were dissatisfied, 6 people (5.16%) said they were neutral, 97 .5 people (84.01%) said they were satisfied and 11.5 people (9.95%) said they were very satisfied. It can be concluded that the majority of respondents expressed satisfaction, and a small percentage stated they were very satisfied. The level of satisfaction is high.